Mitochondrial ROS signalling requires uninterrupted electron flow and is lost during ageing in flies. - Graham, C.; Stefanatos, R.; Yek, A.E.H.; Spriggs, R.V.; Loh, S.H.Y.; Uribe, A.H.; Zhang, T.; Martins, L.M.; Maddocks, O.D.K.; Scialo, F.; Sanz, A. (Geroscience, 2022)
Mitochondrial reactive oxygen species (mtROS) are cellular messengers essential for cellular homeostasis. In response to stress, reverse electron transport (RET) through respiratory complex I generates high levels of mtROS. Suppression of ROS production via RET (ROS-RET) reduces survival under stress, while activation of ROS-RET extends lifespan in basal conditions. Here, we demonstrate that ROS-RET signalling requires increased electron entry and uninterrupted electron flow through the electron transport chain (ETC). We find that in old fruit flies, ROS-RET is abolished when electron flux is decreased and that their mitochondria produce consistently high levels of mtROS. Finally, we demonstrate that in young flies, limiting electron exit, but not entry, from the ETC phenocopies mtROS generation observed in old individuals. Our results elucidate the mechanism by which ROS signalling is lost during ageing.